Pedagogical aspects of the scientific activities of Immanuel Kant (Pedagogy of Higher and Secondary Education, 2012)
Gavrischak I. Pedagogical aspects of the scientific activities of Immanuel Kant.The article investigates pedagogical activity of a famous German philosopher I. Kant, special attention is paid to the treatise «On Pedagogy». The conceptual provisions of the pedagogical foundations of the work were singled out; the analysis of teaching of the German philosopher was made.
Keywords: Immanuel Kant; the University of Knigsberg; pedagogical activity; pedagogical anthropology; education of the individual